2021
DOI: 10.4102/sajhivmed.v22i1.1187
|View full text |Cite
|
Sign up to set email alerts
|

Access to HIV services and viral load suppression among children during the 90-90-90 strategy implementation in South Africa: A time series analysis

Abstract: Background: During the era of the Millennium Development Goals (MDG), children were shown to have less access to human immunodeficiency virus (HIV) services than their adult counterparts; hence the call to prioritise children in the implementation of the Sustainable Development Goals (SDGs). However, South African (SA) national data in 2019 indicated that almost 3 years into the implementation of the 90-90-90 strategy, only 59% of children living with HIV had been tested for HIV compared to 90% of adults.Objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The importance of PLHIV being on an antiretroviral treatment (ART) has been well established, contributing to viral load (VL) suppression as well as reduced odds of advanced HIV disease and mortality. 1,2 Viral load suppression below 1000 copies/mL is an important indicator of successful ART treatment. Innovative techniques to reduce the risk of VL non-supression are of importance during COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of PLHIV being on an antiretroviral treatment (ART) has been well established, contributing to viral load (VL) suppression as well as reduced odds of advanced HIV disease and mortality. 1,2 Viral load suppression below 1000 copies/mL is an important indicator of successful ART treatment. Innovative techniques to reduce the risk of VL non-supression are of importance during COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…[6] The concern is the discrepancy among different age groups, as reported in our previous publication, where children were less likely to be HIV tested and become virally suppressed in CoJ compared with their adult counterparts. [8,9] In addition, men have consistently been reported to lag behind in accessing HIV services over decades, [21,22] and several interventions and innovations to retain them in care have been tried and tested. There is need for more male and children-centred interventions, as they are so far limited.…”
Section: Researchmentioning
confidence: 99%
“…[6] By 2020 the CoJ strategy implementation data showed an improvement in HIV services uptake even though children have been shown to be less likely to access the services and virally suppress compared with their adult counterparts. [8] This calls for action to prioritise children by creating innovative ways to ensure access to HIV services in CoJ and globally. [9] Evidence has shown that ensuring that those who are HIV positive are initiated on ART and virally suppressed will contain the HIV pandemic and reduce transmission, a move towards HIV elimination.…”
mentioning
confidence: 99%
“…We have made mistakes. In aiming at the 2020 targets, children lagged behind, particularly the very young and adolescents, 6 and also young women. The seroprevalence range of antenatal HIV in Soweto, South Africa, is currently at 27% – 30%.…”
mentioning
confidence: 99%